Interaction between Broomrapes and their Hosts - Wahbi Djebali2, Wided Chaibi2, Zouhaier Abbes1,2,*, Mohamed Kharrat1 (Journal of Phytology, 2011)
Broomrapes (Orobanchaceae) are phanerogamic holoparasites that attack the roots of many crops. They vary in host range, some parasitizing a broad range of crops, whereas others are more specific. Broomrape seed germination occurs only in response to a chemical signal from the host root and produces a haustorium which connects directly to the host phloem via contact or transfer cells. The parasite competes successfully with the host sink organs for water and nutrients due to a mechanism assuring a higher osmotic pressure compared with the host plant. Several compatible and incompatible interactions between broomrapes and their hosts have been described. The determination of the osmoregulation and nutritional relationships between broomrapes and their hosts will provide a better understanding of the host-parasite interaction. This can be made by histological, physiological and biochemical or molecular methods which can also allow the development of new methods of control. This review assembles and discusses latest works on the communication and connection between broomrapes and their hosts with particular emphasis on incompatible interactions and osmotic and metabolic particularities of broomrapes in relation with their hosts.